Expression of Matrix Metalloproteinases (MMPs) and Their Tissue Inhibitors (TIMPs) in Frozen Sperm of Rabbit - Sang Hwan Kim; Hwa Sik Choi; Jong Taek Yoon (The Korean Society of Animal Reproduction and Biotechnology, 2019)
We observed MMPs expression in all sperm groups, with pro-MMP showing lower expression than active MMPs. According to the results from each freezing extender, the sperm membrane integrity (HOST: Hypoosmotic Swelling Test) analysis in TCGGD (Tris 250 mM, Citric acid 88 mM, Glucose 47 mM, Glycerol 3%, Dimethylsulpoxide 3.5 M) is 59.8 ± 0.7, TCGSD (Tris 250 mM, Citric acid 88 mM, Glucose 47 mM, Sucrose 0.1 M, Dimethylsulpoxide 3.5 M) is 59.3 ± 0.5 were significantly higher (p < 0.05) among the experimental groups. And MMPs analysis result, we observed MMPs expression in all sperm groups, with pro-MMP showing lower expression than active MMPs. The expression of active MMP-2 was the highest in sperms frozen in TCGSD and TCGD (Tris 250 mM, Citric acid 88 mM, Glucose 47 mM, Dimethylsulpoxide 3.5 M), Meanwhile, sperms from the TCGGD and TCGED (Tris 250 mM, Citric acid 88 mM, Glucose 47 mM, Ethylene glycol 3%, Dimethylsulpoxide 3.5 M) group showed lower level of active MMP-2 expression. Together, these results indicate that adding glycerol or sucrose to the sperm freezing buffer would not only suppress MMPs expression but also minimize DNA fragmentation, providing a mean to improve the success rate in the in vitro manipulation of rabbit sperms. Therefore, these results suggest that TCGGD or TCGSD extender method for freezing-thawing of rabbit sperm increased the viability after thawing.